SOD1 Lysine 123 Acetylation in the Adult Central Nervous System - Kaliszewski, Michael; Kennedy, Austin K.; Blaes, Shelby L.; Shaffer, Robert S.; Knott, Andrew B.; Song, Wenjun; Hauser, Henry A.; Bossy, Blaise; Huang, Ting-Ting; Bossy-Wetzel, Ella (Frontiers in Cellular Neuroscience, 2016)
Superoxide dismutase 1 (SOD1) knockout (Sod1−/−) mice exhibit an accelerated aging phenotype. In humans, SOD1 mutations are linked to familial amyotrophic lateral sclerosis (ALS), and post-translational modification (PTM) of wild-type SOD1 has been associated with sporadic ALS. Reversible acetylation regulates many enzymes and proteomic studies have identified SOD1 acetylation at lysine 123 (K123). The function and distribution of K123-acetylated SOD1 (Ac-K123 SOD1) in the nervous system is unknown. Here, we generated polyclonal rabbit antibodies against Ac-K123 SOD1. Sod1 deletion in Sod1−/− mice, K123 mutation or preabsorption with Ac-K123 peptide all abolished antibody binding. Using immunohistochemistry, we assessed Ac-K123 SOD1 distribution in the normal adult mouse nervous system. In the cerebellum, Ac-K123 SOD1 staining was prominent in cell bodies of the granular cell layer (GCL) and Purkinje cell dendrites and interneurons of the molecular cell layer. In the hippocampus, Ac-K123 SOD1 staining was strong in the fimbria, subiculum, pyramidal cells and Schaffer collateral fibers of the cornus ammonis field 1 (CA1) region and granule and neuronal progenitor cells of the dentate gyrus. In addition, labeling was observed in the choroid plexus (CP) and the ependyma of the brain ventricles and central canal of the spinal cord. In the olfactory bulb, Ac-K123 SOD1 staining was prominent in axons of sensory neurons, in cell bodies of interneurons and neurites of the mitral and tufted cells. In the retina, labeling was strong in the retinal ganglion cell layer (RGCL) and axons of retinal ganglion cells (RGCs), the inner nuclear layer (INL) and cone photoreceptors of the outer nuclear layer (ONL). In summary, our findings describe Ac-K123 SOD1 distribution to distinct regions and cell types of the normal nervous system.